Classification internationale: modèle de développement humain - processus de production du handicap (MDH-PPH) - Cloutier, Chantal; Poulin, Marie-Michelle; Sauvé, Méric; Fougeyrollas, Patrick; Cloutier, René; Bergeron, Hélène; Réseau international sur le processus de production du handicap (RIPPH, Réseau international sur le Processus de production du handicap, 2018)
La Classification internationale : Modèle de Développement humain – Processus de production du handicap (2018) comprend le schéma conceptuel du MDH-PPH, les définitions des domaines conceptuels « habitudes de vie », « facteurs environnementaux » et « facteurs personnels » et leurs différentes nomenclatures. Ce document de référence se révèle utile pour classer l’information disponible de manière cohérente en respectant le principe d’exclusion mutuelle des concepts, central à l’approche du MDH-PPH.
Keywords: EDI; approches et analyses; capacitisme; cours; discipline; médecine; premier cycle; santé; sciences; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

The association between satisfaction with husband's participation in housework and suicidal ideation among married working women in Korea. - Lee, Sang Ah; Park, Eun-Cheol; Ju, Yeong Jun; Han, Kyu-Tae; Yoon, Hyo Jung; Kim, Tae Hyun (Psychiatry research, 2018)
Although married women are increasingly participating in paid labor, housework remains their primary responsibility. This uneven distribution of housework could have a negative impact on their mental health. In this study, we examined the association between satisfaction with husbands' participation in housework and suicidal ideation in married working women. Data were obtained from 3544 participants of the fourth and fifth waves of the Korean Longitudinal Survey of Women and Families. Satisfaction with husbands' participation in housework was classified as satisfactory, less satisfactory, and dissatisfactory. A generalized estimating equations model was used to examine the association. Those who were dissatisfied with their husbands' participation in housework were 2.65 times more likely to think about suicide than those who were satisfied. Subgroup analysis showed that women with an egalitarian gender ideology or low job dissatisfaction were more likely to think about suicide when they were dissatisfied with their husbands' participation in housework. In conclusion, married working women who were dissatisfied with their husbands' participation in housework are more likely to think about suicide than those who are satisfied. Therefore, fostering an environment of fair distribution of housework is necessary for alleviating their stress from the dual burden of work and family. (Copyright © 2018 Elsevier B.V. All rights reserved.)
Keywords: 2000 à aujourd'hui; 2010-2019; asie; charge mentale; corée du sud; discipline; maternité; médecine; projet charge mentale; psychiatrie; périodes historiques; régions géographiques; santé; santé mentale des femmes mariées; suicide; thématiques

The vulva: Physiology and clinical management - Farage, Miranda A.; Maibach, Howard I. (CRC Press, 2017)
Compilation unique d'expertise sur l'anatomie, la physiologie, les questions cliniques et la recherche actuelle, ce manuel analyse la diversité des présentations en fonction de l'âge, de l'origine ethnique, des symptômes, des troubles, des diagnostics et de la toxicité. La deuxième édition de cette ressource essentielle pour toute personne prenant soin de patientes a été doublée pour inclure des chapitres supplémentaires. Tous les médecins, qu'ils soient dermatologues ou gynécologues, ainsi que ceux qui recherchent les preuves scientifiques et les symptômes, bénéficieront de l'expérience des contributeurs et éditeurs experts réunis ici.
Keywords: 2000 à aujourd'hui; corps; dermatologie; discipline; gynécologie; médecine; projet charge mentale; périodes historiques; santé; santé menstruelle; santé reproductive; santé sexuelle; sciences; sexualité; sexualité des femmes*; thématiques

Sex and gender considerations in transplant research: A scoping review - Laprise, Claudie; Cole, Katherine; Sridhar, Vikas Srinivasan; Marenah, Tida; Crimi, Cassandra; West, Lori; Foster, Bethany J.; Pilote, Louise; Sapir-Pichhadze, Ruth (Transplantation, 2017)
Background Despite the growing appreciation of the importance of sex and gender considerations in transplantation research, there is currently no framework or good practice guidelines for the appropriate handling of sex and gender issues in human allotransplantation research. Methods We will conduct a scoping review to synthesize the evidence on how matters of sex and gender have been handled in human allotransplantation research. We will survey the literature discussing sex and gender in relation to transplantation, including adult and pediatric patients, hematopoietic and solid organ transplant recipients as well as organ donors. We will search MEDLINE and Embase for literature discussing sex and gender in relation to transplantation. Two reviewers will independently evaluate the eligibility of all identified titles and abstracts for inclusion in the full text review, as well as data extraction. Descriptive data and information on how sex and gender have been considered in human transplantation research will be reported. Discussion This scoping review will be an important stepping stone towards the development of good practice guidelines on study design and analysis considerations when handling sex and gender issues in human transplantation research. This scoping review can also help identify methodological issues that restrict the translation of transplantation research findings into clinical practice related to underestimation of sex/gender differences. This review will ultimately identify major gaps, inform donor-recipient selection, guide personalized interventions, and prioritize research recommendations in human transplantation research. Electronic supplementary material The online version of this article (10.1186/s13643-017-0578-4) contains supplementary material, which is available to authorized users. Keywords: Sex, Gender, Transplantation, Scoping review
Keywords: 2000 à aujourd'hui; corps; discipline; médecine; projet charge mentale; périodes historiques; ressource en ligne; santé; sciences; thématiques; transplantation

Prendre en compte le sexe et le genre dans le choix des situations à analyser : un enjeu pour l’intervention ergonomique - Laberge, Marie; Caroly, Sandrine (Perspectives interdisciplinaires sur le travail et la santé, 2016)
Le sexe/genre (s/g) doit être pris en compte dans le domaine de la santé au travail, puisque les hommes et les femmes n’occupent pas les mêmes emplois et ne sont pas exposés de la même façon aux risques de santé et sécurité au travail (SST). Cet article propose une réflexion sur les manières de considérer le s/g dans l’intervention ergonomique, en particulier lors des investigations préliminaires. Deux exemples issus d’interventions réalisées en France et au Québec sont présentés. Le premier exemple porte sur l’activité des médecins du travail dans la prévention des troubles musculosquelettiques (TMS). Le second traite du développement et de l’implantation d’une formation portant sur la SST. Dans les deux cas, ces questions portées par les ergonomes chercheuses ont permis de transformer la compréhension des dimensions liées aux parcours de santé, de travail et de vie personnelle pour que la prévention des lésions tienne compte des particularités des hommes et des femmes.
Keywords: amériques; discipline; ergonomie; europe; france; médecine; projet charge mentale; québec; ressource en ligne; régions géographiques; santé; santé au travail; sciences; thématiques; travail

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Gender matters in biological research and medical practice ∗ - Schiebinger, Londa; Stefanick, Marcia L. (Journal of the American College of Cardiology, 2016)
Keywords: 2000 à aujourd'hui; 2010-2019; corps; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; santé; sciences; thématiques

Why sex and gender matter in implementation research - Tannenbaum, Cara; Greaves, Lorraine; Graham, Ian D. (BMC Medical Research Methodology, 2016)
Arrière-plan Les organismes de financement de la recherche en santé et les rédacteurs de revues scientifiques ont récemment intensifié leurs efforts pour accroître la prise en compte des questions de sexe et de genre dans la conception, la conduite et la communication des études afin de garantir que les résultats de la recherche s’appliquent à tous. Cependant, l’examen de la littérature sur la recherche sur la mise en œuvre révèle que l’attention portée au sexe et au genre n’a pas encore infiltré les méthodes de recherche dans ce domaine. Discussion Les raisons pour lesquelles le sexe et le genre sont systématiquement pris en compte dans la recherche sur la mise en œuvre sont multiples. Le sexe et le genre sont importants dans la prise de décision, la communication, l’engagement des parties prenantes et les préférences pour l’adoption des interventions. Les rôles de genre, l’identité de genre, les relations de genre et le genre institutionnalisé influencent la manière dont une stratégie de mise en œuvre fonctionne, pour qui, dans quelles circonstances et pourquoi. De nouvelles preuves montrent que les théories des programmes peuvent fonctionner différemment au sein et entre les sexes, les genres et d’autres caractéristiques intersectionnelles dans diverses circonstances. En outre, sans une étude appropriée, les stratégies de mise en œuvre peuvent exploiter ou ignorer par inadvertance, plutôt que de transformer la réflexion sur le sexe et les facteurs liés au genre. Des techniques sont décrites pour mesurer et analyser le sexe et le genre dans la recherche sur la mise en œuvre en utilisant des méthodes à la fois quantitatives et qualitatives. Résumé Le présent article décrit l’application de méthodes d’intégration du sexe et du genre dans la recherche sur la mise en œuvre. Poser systématiquement des questions critiques sur le sexe et le genre conduira probablement à la découverte de résultats positifs, ainsi que de conséquences imprévues. Le résultat a le potentiel de renforcer à la fois la pratique et la science de la mise en œuvre, d’améliorer les résultats en matière de santé et de réduire les inégalités entre les sexes.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; canada; discipline; médecine; méthodologie; projet charge mentale; périodes historiques; régions géographiques; santé; santé publique; sciences; thématiques; transfert des connaissances

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Minorités sexuelles, Internet et santé - Lévy, Joseph J. (Presses de l'Université du Québec, 2011)
Les nouvelles technologies de communication, et notamment Internet, ont transformé à la fois les stratégies relationnelles et la transmission et le partage des informations dans toutes les sphères de la vie, incluant le domaine de la santé. Pour les minorités sexuelles qui sont confrontées à de multiples formes de discrimination et de marginalisation, Internet est devenu un puissant moyen de s’organiser, d’informer et d’intervenir dans le champ de la santé. Les associations et organismes communautaires ciblant ces populations proposent aujourd’hui un ensemble de sites et de stratégies de soutien et d’intervention. Ces outils synchrones et asynchrones disponibles en ligne visent l’amélioration de la santé mentale et physique, des relations interpersonnelles et la prévention des ITSS et du VIH/sida. Par contre, les usages qui varient en fonction des populations LGBT peuvent aussi concourir à la prise de risques et à des formes de dépendance. Afin de mieux comprendre les enjeux entourant les usages d’Internet et la santé, cet ouvrage, réalisé grâce à l’appui de l’équipe pancanadienne Sexualités et genres ;: vulnérabilité et résilience (SVR), regroupe les contributions de chercheurs de l’équipe qui ont effectué des travaux sur Internet et la santé ainsi que d’intervenants impliqués dans des organismes communautaires, qui utilisent des sites Internet à des fins de réseautage, de transfert d’informations et d’interventions en ligne dans les contextes québécois et canadien.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; internet; militance; médecine; organisme communautaire; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; réseaux sociaux; santé; sciences de la santé; sciences humaines; sexualité; soc2014; système médical; systèmes d'oppressions; thématiques; travail social

Butch/femme, F2M, pregnant man, tranny-boi: Gender issues in the lesbian community - Herbert, Sandra (Journal of Gay and Lesbian Mental Health, 2010)
The author discusses issues pertaining to transgender women and girls. Women identifying as male or transitioning to becoming male are often ignored in the scientific and lay literature on transgender people. The many newer terms for transgender women and girls are discussed, as well as new ways for transgender girls to express their identities. The importance of family and community supports is discussed, and common issues that young transgender people bring into mental health treatment are elucidated.
Keywords: amériques; discipline; identités LGBTQIA2+; médecine; personnes trans*; ressource en ligne; régions géographiques; santé; sciences; thématiques; états-unis